(untitled) (Economic and Political Thought, 2013)
The article presents basic conditions and conclusions of the first in the history of Poland Strategic Review of National Security, which aimed at finding answers to the questions about the overall national security of Poland, formulating a forecast of changes in its conditions in the perspective of 20 years’ time and strategic directions of developing the security of Poland resulting from them. The Strategic Review of National Security was a pioneering initiative. It started a new quality in the development of the Polish strategic culture and attracted a lot of attention at home and abroad. Its success is that it has triggered a widespread debate about security. The success will be complete if the review results in transformational activities aimed at creating an integrated system of national security.